Die gelykenis van die man wat sy buurman gaan opklop het - Lukas 11:5-8 - Stander, H (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
The translation of the Greek word anaideia (“importunity”) forms the crux of the interpretation of this parable. Traditionally this word has been interpreted as describing the person who knocked on the door of his neighbour. The word anaideia is therefore interpreted as “persistence”. The Good News Bible, for example, translates this verse as “because you are not ashamed to keep on asking”. In this article the author shows that the word anaideia is never used by any Church Father in a positive sense. He then argues, based on how the Church Fathers used this word that it rather describes the one who sleeps. The neighbour who was in bed was afraid of being stigmatised as being shameless for not helping his friend. He therefore reluctantly helps his neighbour. Jesus therefore tells this parable to illustrate to his hearers that while people would be willing to help because of wrong motives, God is always ready to hear the prayers of his children. The author also discusses the Church Fathers’ interpretation of this parable. At the end he shows how all the Afrikaans Bible translations misinterpret this verse.